Donor impurity-related photoionization cross section in GaAs cone-like quantum dots under applied electric field. Issue 18 (23rd June 2017) - Iqraoun, E.; Sali, A.; Rezzouk, A.; Feddi, E.; Dujardin, F.; Mora-Ramos, M. E.; Duque, C. A.
Abstract : The donor impurity-related electron states in GaAs cone-like quantum dots under the influence of an externally applied static electric field are theoretically investigated. Calculations are performed within the effective mass and parabolic band approximations, using the variational procedure to include the electron–impurity correlation effects. The uncorrelated Schrödinger-like electron states are obtained in quasi-analytical form and the entire electron–impurity correlated states are used to calculate the photoionisation cross section. Results for the electron state energies and the photoionisation cross section are reported as functions of the main geometrical parameters of the cone-like structures as well as of the electric field strength.